«Un vento gelido di morte che mi pareva a effetto»: sul rapporto Pasolini-Pagliarani - Pozzessere, Giorgio (L’ospite ingrato, 2025)
The essay analyzes the relationship between Pasolini and Pagliarani. While the debate between Pasolini and the Neo-Avant-Garde has been extensively studied, the specific connection with Pagliarani has been less explored. The essay examines their initial poetic and theoretical proximity, and then highlights the divergences that led to their gradual rupture, culminating in the 1960s. The analysis focuses on reviews, correspondence, and mutual references in the works of both authors, emphasizing Pasolini’s role as a critic and promoter of Pagliarani in the early years, and the subsequent distancing. The article also looks at Pagliarani’s later rationalization of their relationship, as evidenced by the poem L’angoscia della tua voce incrinata spezzata da un vento gelido di morte (1995).